Participation in Posbindu PTM and Its Relationship to the Quality of Life of Hypertension Patien - Sari, Nova Nurwinda; Listina, Febria; Maritasari, Dwi Yulia; Fitri, Lisa (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
One of the health problems that has become a serious problem recently is hypertension, which is often referred to as the silent killer because it often occurs without symptoms. Hypertension generally occurs in old age. However, several studies show that hypertension can appear in adolescence and its prevalence has increased in recent years. Many people do not realize this, that hypertension that occurs during adolescence will continue into adulthood and increase the risk of morbidity and mortality. The purpose of this research is to determine the relationship between participation in Posbindu PTM and the quality of life of hypertension sufferers at the Krui Health Center, Pesisir Barat Regency in 2024. A type of quantitative research with an analytical survey research design with a cross sectional approach. Sampling was conducted using purposive sampling with a sample of 95 respondents. The research instrument used was in the form of a questionnaire. This research has been carried out in July 2024 in West Coast Regency. The data analysis used was the spearman's rho test. The results of the study found that there was a relationship between the participation of the PTM posbindu and the quality of life of hypertension patients in the work area of the Krui Health Center with a p-value of 0.000 (p-value < 0.05). Elderly people with hypertension should regularly participate in PTM posbindu activities as an effort to control hypertension and help improve the quality of life of the elderly.